EVALUASI KARAKTER AGRONOMI KELAPA SAWIT (Elaeis guineensis Jacq.) VARIETAS DXP AVROS PADA KONDISI CEKAMAN KEKERINGAN DI MAIN NURSERY - Eka Bobby Febrianto; Sri Murti Tarigan; Igo Azri (Bernas : Jurnal Penelitian Pertanian, 2019)
Palm oil (Elaeis guineensis Jacq.) is Indonesia's leading and prime plantation commodity. The main products are palm oil (CPO) or palm kernel oil (KPO). Both of these products have high economic value and become one of the largest foreign exchange earners compared to other plantation commodities. Until now palm oil has been cultivated in the form of oil palm plantations and processing plants to become oil and derivative products. The study was carried out in the STIPAP greenhouse. The research period was 7 months, from September to March 2018. This research used Factorial 1 design with 3x replication, the number of polybags per treatment was 3. Parameter testing was arranged on the variance list and Duncan's Multiple Range Test (DMRT) was tested at level 5 %. The results showed that the DxP Avros variety had good adaptability to water stress, especially on stem diameter, leaf number, leaf area, amount of chlorophyll, number of roots, root length, number of stomata not significantly different between treatments A1, A2 and A3.